Structural and vibrational properties and NMR characterization of (2’-furyl)-imidazole compounds - Ledesma, Ana Estela (2012)
The furylimidazoles compounds have a great importance in biochemistry and pharmacology because many of them present interesting properties. They are also found in artificial compounds, such as agrochemicals, pharmaceuticals, dyes, plastics, solvents, photographic chemicals, electronics, corrosion inhibitors, preservatives, and polymers. They can be used in synthetic organic chemistry as building blocks, due to their presence as key structural units in many natural products and in important pharmaceuticals. For example, the nature of the N- atoms in the imidazole molecule makes possible an extraordinary variety of reactions and this is the main reason for the great biological importance of the amino acid, histidine.